Feed and feeding of fish and shrimp : - New, Michael B. (FAO, 1987)
This manual is intended to be an easy-to-read guide to the selection manufacture, storage, and use of feed in small-scale aquaculture. It concentrates on feed for fingerling fish and postlarval shrimp/prawns up to market-size animals, it does not cover hatchery or live feeds, or fertilization techniques, which are the subject of other FAO manuals.